Ion exchange nanofiber membrane with high ion removal effect and preparation method

By preparing β-cyclodextrin/PVDF composite film, the problem of low adsorption performance of electrospinned fiber membranes is solved, and Cu2+ is efficiently removed in dye wastewater, significantly improving the adsorption capacity.

CN119793421APending Publication Date: 2025-04-11ZHEJIANG SCI-TECH UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411968407.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing electrospinning fiber membranes have low adsorption performance and it is difficult to effectively remove metal ions in dye wastewater.

Method used

Using a β-cyclodextrin/PVDF composite film, an ion exchange nanofiber membrane with high porosity and strong mechanical properties was prepared by mixing PVDF powder with dimethylformamide and β-cyclodextrin, electrospinning and in-situ thermal crosslinking.

Benefits of technology

The liquid absorption and porosity of the nanofiber membrane are improved, and the adsorption capacity to Cu2+ is significantly enhanced, reaching an adsorption amount of 182.65 mg·g-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793421A_ABST
    Figure CN119793421A_ABST
Patent Text Reader

Abstract

The invention provides an ion exchange nanofiber membrane with a high ion removal effect and a preparation method of the ion exchange nanofiber membrane, and the preparation method comprises the following steps: 1) adding PVDF powder into a container containing dimethyl formamide (DMF), and stirring to obtain a PVDF solution; 2) adding beta-cyclodextrin, namely beta-CD, into the PVDF solution, performing ultrasonic treatment and stirring to obtain a beta-CD / PVDF mixed electrostatic spinning solution, and performing electrostatic spinning by taking the beta-CD / PVDF mixed electrostatic spinning solution as a raw material to obtain a fiber membrane; (3) carrying out in-situ thermal crosslinking on the fiber film to obtain a beta-cyclodextrin / PVDF composite film; the adsorption capacity of the beta-CD / PVDF composite membrane on Cu < 2 + > is increased to 182.65 mg.g <-1 >. The beta-CD / PVDF composite film can be used as a composite film for adsorbing Cu < 2 + >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to an ion exchange nanofiber membrane with high ion removal effect and a preparation method thereof. Background Art

[0002] With the growing development of printing and dyeing, textile and other industries, the dye wastewater discharged enters rivers, lakes, seas and groundwater, causing irreversible damage to the human body. At present, the methods for treating dye wastewater at home and abroad are mostly physical adsorption, biological methods, chemical oxidation and membrane separation. Adsorption technology has attracted widespread attention due to its low adsorption cost, universal applicability to various pollutants and convenient operation. The nanofiber membrane prepared by electrospinning has the characteristics of small fiber diameter, large specific surface area, tortuous pore channels, high porosity, small pore size and high surface energy. It has ultra-high removal characteristics for small particles, that is, high filtration efficiency and large adsorption capacity.

[0003] Patent publication number CN115591417A discloses a composite membrane capable of purifying dye wastewater and a preparation method thereof. The composite membrane capable of purifying dye wastewater is composed of graphene oxide and polyacrylonitrile fibers; graphene oxide is interspersed between staggered and stacked polyacrylonitrile fibers to form a three-dimensional network support structure; the composite membrane capable of purifying dye wastewater has a porosity of 18% to 27% and a water flux of 330 to 850 L / m 2 h, specific surface area is 15~400m 2 / g; the preparation method is: conjugate electrospinning of an inorganic dispersion of graphene oxide and a polyacrylonitrile solution to obtain a composite membrane that can purify dye wastewater. Patent Publication No. CN112376166A discloses a method for preparing a carbon nanotube-modified polyacrylonitrile nanofiber membrane and its application, using acrylonitrile, 2-methylene-4-phenyl-1,3-dioxolane, methyl methacrylate silane, initiator and solvent to prepare modified polyacrylonitrile by free radical polymerization; then electrospinning is used to prepare a carbon nanotube-modified polyacrylonitrile nanofiber membrane. Although a series of methods for improving the adsorption performance of fiber membranes by doping inorganic nanoparticles such as graphene oxide, carbon nanotubes, and zinc oxide are disclosed in the prior art, the adsorption amount is still low, and the adsorption performance needs to be further improved. Summary of the invention

[0004] In order to solve the technical problem of poor adsorption performance of electrospun fiber membranes, the present invention proposes an ion exchange nanofiber membrane with high ion removal effect and a preparation method. The nanofiber membrane prepared by the present invention has the characteristics of large surface area, high porosity, strong mechanical properties and excellent ion adsorption and removal performance.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing an ion exchange nanofiber membrane with high ion removal effect, comprising the steps of:

[0007] 1) adding PVDF powder into a container containing dimethylformamide (DMF) and stirring to obtain a PVDF solution;

[0008] 2) adding β-cyclodextrin (β-CD) to the PVDF solution, ultrasonicating and stirring to obtain a β-CD / PVDF mixed electrospinning solution, and performing electrospinning using the β-CD / PVDF mixed electrospinning solution as a raw material to obtain a fiber membrane;

[0009] 3) The fiber membrane is subjected to in-situ thermal cross-linking to obtain a β-cyclodextrin / PVDF composite film.

[0010] Furthermore, in step 1), the stirring condition is magnetic stirring at 360 rpm at room temperature for at least 4 hours, and the mass concentration of PVDF in the PVDF solution is 10%.

[0011] Furthermore, the mass concentration of β-CD in the β-CD / PVDF mixed electrospinning solution is 1-3%, and the solution is ultrasonically dispersed for 30 seconds at room temperature and stirred for 1 hour. The preferred concentration of β-CD is 3%.

[0012] Furthermore, during the electrospinning process, the raw material was injected into a 10 ml syringe, and the electrospinning parameters were adjusted to a working voltage of 18 kV, a collector distance of 15 cm, and a flow rate of 1 ml h -1 .

[0013] Furthermore, the in-situ thermal crosslinking condition is at 140° C. for at least 2 hours.

[0014] A highly efficient adsorption of Cu 2+ The β-cyclodextrin / PVDF composite film is obtained by any of the methods described above.

[0015] Furthermore, the liquid absorption rate of the β-cyclodextrin / PVDF composite film is 357.17% to 439.38%, and the porosity is 69.34% to 79.56%.

[0016] An ion exchange nanofiber membrane with high ion removal effect, namely the β-cyclodextrin / PVDF composite film, the metal ion is Cu 2+ .

[0017] Beneficial effects of the present invention:

[0018] The β-CD / PVDF composite film is smooth and randomly deposited to form an interconnected three-dimensional network structure. The diameter of the β-CD / PVDF composite film is between 0.22 and 0.33 μm, and the fiber diameter is evenly distributed, which makes the film have a larger specific surface area. When the β-CD content is 3%, the maximum porosity is 79.56%. With the increase of β-CD content, the β-CD / PVDF composite film has a higher porosity than the Cu 2+ The adsorption capacity increased to 182.65 mg·g -1 .

[0019] In addition, the second-order kinetic model is suitable for describing the adsorption process. Due to the presence of β-CD, chemical adsorption is the main mechanism of the adsorption process. The results show that β-CD / PVDF composite film can be used as a Cu adsorption 2+ of composite film. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is a graph showing the relationship between β-CD content and conductivity in an embodiment of the present invention;

[0022] Figure 2 This is a graph showing the relationship between β-CD content and viscosity in an embodiment of the present invention;

[0023] Figure 3 The scanning electron micrographs of PVDF composite films with different β-CD contents in the embodiments of the present invention are as follows: (a) PVDF, (b) 1% β-CD / PVDF, (c) 2% β-CD / PVDF, (d) 3% β-CD / PVDF;

[0024] Figure 4 Fiber diameter distribution of PVDF composite films with different β-CD contents in the embodiments of the present invention: (a) PVDF, (b) 1% β-CD / PVDF, (c) 2% β-CD / PVDF, (d) 3% β-CD / PVDF;

[0025] Figure 5 The β-CD / PVDF composite films with different β-CD contents in the embodiment of the present invention have a significant effect on Cu 2+ Absorption efficiency curve;

[0026] Figure 6The β-CD / PVDF composite films with different β-CD contents in the embodiment of the present invention have a significant effect on Cu 2+ The absorption curve of . DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] PVDF powder was placed in a glass bottle containing dimethylformamide (DMF) to prepare a PVDF solution with a mass concentration of 10%. Then, magnetic stirring was performed at 360 rpm for 4 hours at room temperature until the mixture was uniform. β-CD powder was added to the PVDF solution to make its mass concentration reach 1%. After ultrasonic dispersion, the mixture was stirred to obtain a homogeneous solution, β-CD / PVDF mixed electrospinning solution. The electrospinning solution was injected into a 10 ml syringe, and the electrospinning parameters were adjusted to a working voltage of 18 kV, a collector distance of 15 cm, and a flow rate of 1 ml h. -1 Subsequently, the fiber membrane obtained by electrospinning was placed in a vacuum drying oven for in-situ thermal crosslinking to make β-CD insoluble in water, which was beneficial for the film properties to be more stable during the adsorption process. Finally, the thermal crosslinking condition of the β-cyclodextrin / PVDF composite film was 140°C and the treatment lasted for 2h.

[0030] Example 2

[0031] PVDF powder was placed in a glass bottle containing dimethylformamide (DMF) to prepare a PVDF solution with a mass concentration of 10%. Then, magnetic stirring was performed at 360 rpm for 4 hours at room temperature until the mixture was uniform. β-CD powder was added to the PVDF solution to make its concentration reach 2%. After ultrasonic dispersion, the mixture was stirred to obtain a homogeneous solution, β-CD / PVDF mixed electrospinning solution. The electrospinning solution was injected into a 10 ml syringe, and the electrospinning parameters were adjusted to an operating voltage of 18 kV, a collector distance of 15 cm, and a flow rate of 1 ml h. -1 Subsequently, the fiber membrane obtained by electrospinning was placed in a vacuum drying oven for in-situ thermal crosslinking to make β-CD insoluble in water, and finally a β-cyclodextrin / PVDF composite film was obtained. The thermal crosslinking condition was 140°C and the treatment lasted for 2 hours.

[0032] Example 3

[0033] PVDF powder was placed in a glass bottle containing dimethylformamide (DMF) to prepare a PVDF solution with a mass concentration of 10%. Then, magnetic stirring was performed at 360 rpm for 4 hours at room temperature until the mixture was uniform. β-CD powder was added to the PVDF solution to make its concentration reach 3%. After ultrasonic dispersion, the mixture was stirred to obtain a homogeneous solution, β-CD / PVDF mixed electrospinning solution. The electrospinning solution was injected into a 10 ml syringe, and the electrospinning parameters were adjusted to an operating voltage of 18 kV, a collector distance of 15 cm, and a flow rate of 1 ml h. -1 Subsequently, the fiber membrane obtained by electrospinning was placed in a vacuum drying oven for in-situ thermal crosslinking to make β-CD insoluble in water, and finally a β-cyclodextrin / PVDF composite film was obtained. The thermal crosslinking condition was 140°C and the treatment lasted for 2 hours.

[0034] Comparative Example

[0035] PVDF powder was placed in a glass bottle containing dimethylformamide (DMF) to prepare a PVDF solution with a mass concentration of 10%. Then, magnetic stirring was performed at 360 rpm for 4 h at room temperature until the mixture was uniform. The electrospinning solution was injected into a 10 ml syringe, and the electrospinning parameters were adjusted to an operating voltage of 18 kV, a collector distance of 15 cm, and a flow rate of 1 ml h. -1 , and obtain PVDF film.

[0036] Results and Discussion

[0037] according to Figure 1 and 2 It can be seen that during the electrospinning process, the properties of the solution (including viscosity, conductivity, etc.) have a significant effect on the morphology and diameter of the fiber. The conductivity and viscosity of PVDF solutions with different β-CD contents were measured using a conductivity meter (DDS-11A) and a viscometer (NDJ-79A), respectively. The results were repeated three times and the average values ​​were obtained. Figure 1 The conductivity of β-CD / PVDF solution with different β-CD concentrations is shown. When the β-CD concentration is 0, the conductivity of PVDF solution is 9.52 μS cm -1 As the concentration of β-CD increases, the conductivity decreases significantly. However, when the concentration of β-CD is increased to 3%, the conductivity of the β-CD / PVDF solution at a concentration of 2% increases from 6.67 μS cm -1 Increased to 7.45 μS cm -1 , Due to the unique molecular structure of β-CD, the hollow interior of β-CD may promote the transfer of electrons within the molecule, thereby affecting the overall conductivity of β-CD / PVDF solution. Figure 2The viscosity of β-CD / PVDF solutions with different β-CD contents is shown. The viscosity of the PVDF solution is 1590 mPa·s, while as the β-CD content increases from 1% to 3%, the viscosity of the β-CD / PVDF solution decreases from 1770 mPa·s to 1320 mPa·s. This result can be attributed to the presence of β-CD, which is believed to affect the intermolecular forces between polymer molecules, thereby affecting its viscosity. It can be seen that the addition of β-CD changes the viscosity and conductivity of the solution, resulting in a decrease in the charge distribution on the surface of the electrospinning solution, which in turn affects the morphology of the fiber, causing the diameter of the β-CD / PVDF composite film fiber to increase with the increase of the β-CD content.

[0038] Scanning SEM images and fiber diameter distribution of β-CD / PVDF composite nanofiber films with different β-CD contents are shown in Figure 2. Figure 3 and 4 As shown. Figure 3 It can be seen that the fibers are relatively smooth and randomly deposited, forming an interconnected three-dimensional network structure. Figure 4 (a) It can be seen that the average diameter of PVDF fiber is the smallest, as small as 0.22μm. Its standard deviation is also the smallest, as small as 0.06μm, indicating that the fiber diameter distribution is relatively uniform. The diameter of β-CD / PVDF composite film fiber increases with the increase of β-CD content. There may be two reasons for this phenomenon. On the one hand, with the addition of β-CD, the conductivity of β-CD / PVDF solution decreases, such as Figure 1 As shown in Figure 2, as the conductivity of β-CD / PVDF decreases, the electric field force on the jet gradually decreases, and the final fiber diameter gradually increases. On the other hand, the presence of β-CD changes the viscosity of the β-CD / PVDF solution, as shown in Figure 2. Figure 2 This is because β-CD can increase the degree of molecular chain entanglement.

[0039] The liquid absorption rate and porosity of the composite film have a significant effect on the adsorption performance of metal ions. The liquid absorption rate of the composite film was determined by the water absorption method, and the porosity of the composite film was determined by the ethanol replacement method. The corresponding results are summarized in Table 1. As can be seen from Table 1, the liquid absorption rate of the PVDF film is 289.82% and the porosity is 63.37%. As the β-CD concentration increases from 1% to 3%, the liquid absorption rate increases from 357.17% to 439.38%, and the porosity increases from 69.34% to 79.56%, respectively. Higher liquid absorption rate and porosity are conducive to improving the adsorption performance of the film. This is because the film has more porous structures and active surface sites, which provides more contact opportunities for metal ions and the film. In addition, the higher the liquid absorption rate, the more it promotes the migration and diffusion of metal ions from the surface of the composite film to the inside of the composite film, thereby increasing the adsorption rate of metal ions.

[0040] Table 1

[0041]

[0042]

[0043] To test the adsorption capacity, 10 mg of β-CD / PVDF composite film was added to a solution with a concentration of 400 mg g -1 In copper sulfate solution. Take 3 ml of the solution every 2 hours and measure the absorbance of the solution at a wavelength of 480 nm using a spectrophotometer. Figure 5 and Figure 6 The results show that the different contents of β-CD / PVDF composite films have an influence on the Cu 2+ The adsorption efficiency curve and adsorption amount curve of the curve. It can be seen that with the increase of time, the β-CD / PVDF composite film has a 2+ The adsorption efficiency of CuO2 is continuously improved and gradually reaches equilibrium. This phenomenon is due to the presence of a large number of active sites on the film surface and the initial stage of CuO2. 2+ The concentration gradient of β-CD is high, which binds to the active sites and promotes a rapid reaction. However, as the adsorption time increases, these active sites are gradually occupied, causing them to gradually approach equilibrium. Compared with PVDF membrane, the addition of β-CD significantly improves the β-CD / PVDF composite film for Cu 2+ The adsorption efficiency of β-CD is high, and its adsorption efficiency gradually increases with the increase of β-CD content. This is attributed to the unique three-dimensional inclusion structure of β-CD. β-CD has a hydrophobic cavity inside and a hydrophilic hollow truncated cone structure on the outer surface. The hydrophobic cavity of β-CD can effectively form a host-guest inclusion body with heavy metal ions in water, thereby removing heavy metal ions from water. In addition, Cu 2+ The adsorption of Cu also involves two processes. First, 2+ When the concentration of β-CD reaches 3%, the β-CD / PVDF composite film has a strong adsorption capacity for Cu 2+ The adsorption capacity can reach up to 182.65 mg g -1 .

[0044] The embodiments described above provide a detailed description of the preparation scheme of the present invention. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An ion exchange nanofiber membrane with high ion removal effect and a preparation method thereof, characterized in that the steps include: 1) adding PVDF powder into a container containing dimethylformamide (DMF) and stirring to obtain a PVDF solution; 2) adding β-cyclodextrin (β-CD) to the PVDF solution, ultrasonicating and stirring to obtain a β-CD / PVDF mixed electrospinning solution, and performing electrospinning using the β-CD / PVDF mixed electrospinning solution as a raw material to obtain a fiber membrane; 3) The fiber membrane is subjected to in-situ thermal cross-linking to obtain a β-cyclodextrin / PVDF composite film, which can efficiently remove Cu ions in the solution.

2. The preparation method according to claim 1, characterized in that: In step 1), the stirring condition is magnetic stirring at 360 rpm at room temperature for at least 4 hours, and the mass concentration of PVDF in the PVDF solution is 10%.

3. The preparation method according to claim 1, characterized in that: In step 2), the concentration of β-CD in the β-CD / PVDF mixed electrospinning solution is 1-3%, and the solution is ultrasonically dispersed at room temperature for 30 seconds and stirred for 1 hour.

4. The preparation method according to claim 1, characterized in that: In step 2), during the electrospinning process, the raw material was injected into a 10 ml syringe, and the electrospinning parameters were adjusted to a working voltage of 18 kV, a collector distance of 15 cm, and a flow rate of 1 ml h -1 .

5. The preparation method according to claim 1, characterized in that: In step 3), the in-situ thermal crosslinking condition is at 140° C. for at least 2 hours.

6. A highly efficient adsorption of Cu 2+ The β-cyclodextrin / PVDF composite film is characterized in that The method is obtained by any one of claims 1 to 5.

7. The β-cyclodextrin / PVDF composite film according to claim 6, characterized in that: The liquid absorption rate of the beta-cyclodextrin / PVDF composite membrane is 357.17% to 439.38%, and the porosity is 69.34% to 79.56%.

8. Use of the β-cyclodextrin / PVDF composite film according to claim 6 or 7 in the treatment of wastewater containing metal ions, characterized in that: The metal ion is Cu 2+ .

Citation Information

Patent Citations

  • Preparation method and application of carbon nanotube-modified polyacrylonitrile nanofiber membrane

    CN112376166A

  • Composite membrane capable of purifying dye wastewater and preparation method thereof

    CN115591417A